Globalization and Its Role in the Development of Post-Soviet Higher Education Institutions (on the Example of Ivane Javakhishvili Tbilisi State University) - Tvaltvadze, Darejan; Gvelesiani, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
“The impact of the various trends and challenges related to globalisation of higher education institutions and policies is profound, but also diverse, depending on the specific location in the global arena” (Damme, 2010). The given paper is dedicated to the study of globalizing processes and their influence on the development of Georgian Post-Soviet higher education area. The contemporary educational strategies are highlighted on the example of Ivane Javakhishvili Tbilisi State University – the leading educational institution of the whole Caucasus region. During the recent years Tbilisi State University underwent significant innovative processes comprising the following major directions: Internationalization – establishment of foreign centers; implementation of joint projects and exchange programs; creation of international winter and summer schools; Modernization – implementation of 4-level studies; creation of encyclopedic dictionary; restructuring faculties; redirection of scientific researches, etc. The significance of the above mentioned innovations, their impact on the development of Post-Soviet university life and Georgians’ steps made towards the rapid integration into the European educational space – these are contemporary strategic issues and major challenges of our work. The highlighted strategies can serve as an exemplary and useful model of progress for those Post-Soviet universities of the world, which strive to join the European Higher Education Area.